Tools for Change: Measuring Student Conceptual Understanding Across Undergraduate Biology Programs Using Bio-MAPS Assessments - Michelle K. Smith (American Society for Microbiology, 2019)
Assessing learning across a biology major can help departments monitor achievement of broader program-level goals and identify opportunities for curricular improvement. However, biology departments have lacked suitable tools to measure learning at the program scale. To address this need, we developed four freely available assessments—called Biology-Measuring Achievement and Progression in Science or Bio-MAPS—for general biology, molecular biology, ecology/evolution, and physiology programs. When administered at multiple time points in a curriculum, these instruments can provide departments with information on how student conceptual understanding changes across a major and help guide curricular modifications to enhance learning.